Risks worker health in rapadura production (Research, Society and Development, 2020)
The objective of the study was to describe the productive process of rapadura and to evaluate risks to health of rural worker in the sugar cane mill. It’s a descriptive research, of case study type, developed in municipality of Tianguá, Ceará, Brazil, from August to September 2018, with workers from a sugar cane mill. Data collection was based on observation and semi-structured interview with four subjects through a semi-structured interview, based on the International Labor Organization's framework. In all stages of production there was some risk involved, the main ones referring to biological, chemical and ergonomic risk. The findings indicate that workers are daily exposed to risks and they are unaware of importance of using PPE, as well as, the company does not promote worker safety. Thus, further studies about risks and harms to health of sugar mill workers are necessary to implement safety measures at their work, avoiding possible damages that could compromise their health and quality of life.